Nonaqueous Sodium‐Ion Full Cells: Status, Strategies, and Prospects - Niu, Yu‐Bin; Yin, Ya‐Xia; Guo, Yu‐Guo (Small (Weinheim an der Bergstrasse, Germany), 2019)
With ever‐increasing efforts focused on basic research of sodium‐ion batteries (SIBs) and growing energy demand, sodium‐ion full cells (SIFCs), as unique bridging technology between sodium‐ion half‐cells (SIHCs) and commercial batteries, have attracted more and more interest and attention. To promote the development of SIFCs in a better way, it is essential to gain a systematic and profound insight into their key issues and research status. This Review mainly focuses on the interface issues, major challenges, and recent progresses in SIFCs based on diversified electrolytes (i.e., nonaqueous liquid electrolytes, quasi‐solid‐state electrolytes, and all‐solid‐state electrolytes) and summarizes the modification strategies to improve their electrochemical performance, including interface modification, cathode/anode matching, capacity ratio, electrolyte optimization, and sodium compensation. Outlooks and perspectives on the future research directions to build better SIFCs are also provided. Sodium‐ion full cells with low cost and abundant resource are promising to satisfy the urgent demand of large‐scale energy storage, yet their developments suffer from challenges of interfacial characteristics. Here, their recent advances in various electrolytes are summarized, and diverse strategies including tailoring interface, matching capacity, optimizing electrolyte as well as compensating sodium to drive the development of the whole industry are addressed.